2000
DOI: 10.12968/bjom.2000.8.1.8198
|View full text |Cite
|
Sign up to set email alerts
|

Informed choice in maternity services

Abstract: The aim of this study was to investigate informed choice in relation to care-giver and location of care, within maternity services in Powys. The study utilized a survey design, eliciting both quantitative and qualitative data from respondents. The aims of the research were to evaluate women's perceptions of the quantity and quality of information received, to highlight examples of good practice and to identify potential areas of concern. The results demonstrated high levels of satisfaction with the amount of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The present study, like a number of others, [22][23][24][25] has shown that there is a gap between the information women want about tests during pregnancy and the information provided by health professionals. Although the data in the present study were collected from women an average of two months after the event, and therefore could reflect faulty recall, they accord with observational studies [26][27][28] and support the pattern of results reported elsewhere, 29 including a Health Technology Assessment review on 'Psychosocial aspects of genetic screening of pregnant women and newborns', which very clearly shows that lack of understanding within this context is widespread.…”
Section: Discussionsupporting
confidence: 51%
“…The present study, like a number of others, [22][23][24][25] has shown that there is a gap between the information women want about tests during pregnancy and the information provided by health professionals. Although the data in the present study were collected from women an average of two months after the event, and therefore could reflect faulty recall, they accord with observational studies [26][27][28] and support the pattern of results reported elsewhere, 29 including a Health Technology Assessment review on 'Psychosocial aspects of genetic screening of pregnant women and newborns', which very clearly shows that lack of understanding within this context is widespread.…”
Section: Discussionsupporting
confidence: 51%
“…Twelve studies used samples that were described as ‘all’ who were eligible within a given timeframe. For example, ‘all first‐time mothers in Powys ( n = 445) who delivered during the 10‐month period’ (Churchill & Benbow 2000, p. 42).…”
Section: Critiquing the Studiesmentioning
confidence: 99%
“…It was mentioned explicitly in studies such as those of Hallgren et al (1995) on childbirth education and Webster et al (1995) looking at patterns of care to suit women's needs, and was implied in studies such as Stewart (1999), who concluded that the culture of midwifery practice should change to accept lesbian mothers. Informed choice and decision-making was again implicit in many studies but was a major factor in Churchill and Benbow's (2000) report; this suggested that women had more opportunities for informed choice and decision-making about care in general practitioner/midwife units than in consultant obstetrician units.…”
Section: Organization Of Servicesmentioning
confidence: 99%
“…Researchers working from a cognitive perspective test patients' knowledge of the issues at hand or solicit their self-reports of feeling adequately informed (Freda, DeVore, Valentine-Adams, Bombard, & Merkatz, 1998;Gourounti & Sandall, 2008;Kohut, Dewey, & Love, 2002;O'Cathain, Thomas, Walters, Nicholl, & Kirkham, 2002;Rowe, Fisher, & Quinlivan, 2006;Shorten, Shorten, Keogh, West, & Morris, 2005;van den Berg, Timmermans, Ten Kate, van Vugt, & van der Wal, 2006). Patients may also evaluate the quality and quantity of information provided (Churchill & Benbow, 2000;Guillemin & Gillam, 2006).…”
Section: Problem Statementmentioning
confidence: 99%